Увеличение срока службы режущего инструмента - Гладкова, В. И. (НТУ "ХПИ", 2003)
In the article the experiments results at to increasing the service period of the cut tool by drifting the plasma covers by CIB-method and influence the liquid boride method are presented. The drawn a conclusion about advisable using methods in industry
Keywords: металлические изделия; метод плазменного напыления; вакуумная установка «Булат»; метод жидкостного борирования; боридные слои